Bioactivation of trichloroethylene to three regioisomeric glutathione conjugates by liver fractions and recombinant human glutathione transferases: Species differences and implications for human risk assessment. (1st May 2021) - Capinha, Liliana; Jennings, Paul; Commandeur, Jan N.M.
Graphical abstract: Highlights: First HPLC-method for the analysis of regioisomers of S-conjugates of trichloroethylene (TCE). TCE is metabolized to three regioisomeric GSH-conjugates by rat and human liver. Big difference in rate and regioselectivity of GSH-conjugation of TCE between rat and human. Activity and regioselectivity of conjugation by eleven human glutathione transferases. Abstract: Enzymatic conjugation of glutathione (GSH) to trichloroethylene (TCE) followed by catabolism to the corresponding cysteine-conjugate, S-(dichlorovinyl)-L-cysteine (DCVC), and subsequent bioactivation by renal cysteine conjugate beta-lyases is considered to play an important role in the nephrotoxic effects observed in TCE-exposed rat and human. In this study, it is shown for the first time that three regioisomers of GSH-conjugates of TCE are formed by rat and human liver fractions, namely S-(1, 2-trans-dichlorovinyl)-glutathione (1, 2-trans-DCVG), S-(1, 2-cis-dichlorovinyl)-glutathione (1, 2-cis-DCVG) and S-(2, 2-dichlorovinyl)-glutathione (2, 2-DCVG). In incubations of TCE with rat liver fractions their amounts decreased in order of 1, 2-cis-DCVG > 1, 2-trans-DCVG > 2, 2-DCVG. Human liver cytosol showed a more than 10-fold lower activity of GSH-conjugation, with amounts of regioisomers decreasing in order 2, 2-DCVG > 1, 2-trans-DCVG > 1, 2-cis-DCVG. Incubations with recombinant human GSTs suggest that GSTA1-1 and GSTA2-2 play the most important role in human liver cytosol. GSTP1-1, which produces regioisomers in order 1, 2-trans-DCVG > 2, 2-cis-DCVG > 1, 2-cis-DCVG, is likely to contribute to extrahepatic GSH-conjugation of TCE. Analysis of the products formed by a beta-lyase mimetic model showed that both 1, 2-trans-DCVC and 1, 2-cis-DCVC are converted to reactive products that form cross-links between the model nucleophile 4-(4-nitrobenzyl)-pyridine (NBP) and thiol-species. No NBP-alkylation was observed with 2, 2-DCVC corresponding to its low cytotoxicity and mutagenicity. The lower activity of GSH-conjugation of TCE by human liver fractions, in combination with the lower fraction of potential nephrotoxic and mutagenic 1, 2-DCVG-isomers, suggest that humans are at much lower risk for TCE-associated nephrotoxic effects than rats.